Counterfactual model for labour market evaluation policies - Emilio Colombo; Mario Mezzanzanica; Giampaolo Montaletti; Gloria Ronzoni (European Regional Science Association (ERSA), 2015)
This paper presents the methodological approach used to analyse and assess an active labour market policy called Dote Unica del Lavoro (DUL) implemented by the Lombardy Region with reference to the period October 2013-June 2014 and addressed to 25 thousand beneficiaries. The aim of the project is to assess and quantify the efficiency of the policy measured by the labour market outcomes of the beneficiaries. The methodology is based on the counterfactual non experimental approach using the Propensity Score Matching technique. The technique is based on the comparison of the outcomes of two groups of individuals: beneficiaries and non beneficiaries (i.e. exposed and non exposed in the terminology of medical treatment) of the public employment policy. The key point is the identification and selection of the group of non beneficiaries (non exposed) that ideally should share the same features and characteristics of the beneficiaries (exposed) so that the change in outcome of the beneficiaries (if detected) can be attributed to the policy and not to other confounding factors.
Keywords: 330